Masyarakat Global dalam Ketahanan Nasional Melalui Menjaga Identitas, Stabilitas, dan Kedaulatan - Aimatus Sharoh; Wulan Mega Mustika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Globalization accelerates the flows of goods, capital, information, and culture, creating development opportunities while also generating risks for national resilience. This study maps the conditions and mechanisms through which engagement in global society can weaken or, conversely, strengthen resilience across three dimensions—identity, stability, and sovereignty. Using a PRISMA-guided systematic literature review, bilingual searches were conducted in reputable Indonesian journals (UGM, Unhan, Lemhannas, BRIN, Unair, UNS) covering 2015–2025. Screening included deduplication, title/abstract selection, full-text assessment, and CASP/JBI quality appraisal, followed by thematic synthesis. Through database searching and snowballing, 20 articles were analyzed. The review highlights three key findings: (1) information–cyber resilience is a prerequisite, as low digital literacy and weak cyber hygiene increase the likelihood of disinformation and incident escalation; (2) digital politics is ambivalent—expanding participation yet fostering selective exposure and polarization; and (3) sovereignty increasingly shifts toward data, technology, and the policy space. Overall, global society’s impact is not deterministic; it depends on policy design, institutional capacity, and citizen participation. Strengthening literacy, platform governance, cybersecurity, cultural diplomacy, and value-added industrial policies is recommended.